STUDENT’S PERCEPTION OF THE STEM FAIR AT PHNOM PENH TEACHER EDUCATION COLLEGE (PTEC) DURING THE 2023-2024 ACADEMIC YEAR - Reth, Phearun; Mom, Putheary; Srieng, Kimsron (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
Student enrollment in STEM-related disciplines is low across the nation. Students from rural locations with little access to STEM enrichment programs and marginalized demographics should be especially aware of this. This study aimed to investigate how students perceive on STEM Fair and how gender, age, experience, and needs relate to its requirements. The study's population was made up of students from different Phnom Penh schools. There were 242 pupils in the sample. This quantitative study explored students' perceptions of STEM and the effects of the STEM Fair on them. The study employed questionnaires to assess students' interest, knowledge gain, and social self-efficacy. Student participants at the STEM Fair provided survey responses. SPSS 22 was used for data analysis. First, it was discovered that students' perceptions of STEM were characterized by a greater number of constructive and positive comments than unfavorable ones. It is possible that a bigger percentage of positive items in the research sample will signal or guarantee an improvement in participants' impressions of STEM fair. Second, a Chi Square test for independence was used to examine the relationship between the criteria of the STEM Fair and three specific characteristics: gender, age, and experience. The Chi Square results showed that there was insufficient proof to connect the three components to the requirements of the STEM Fair. The information supplied here supports the findings that STEM Fairs increase positive attitudes about STEM and increase STEM knowledge, yet the following useful recommendations are made for future STEM study.